ECB Consumer Expectations Survey: An overview and first evaluation - Katarzyna Bańkowska; Ana Maria Borlescu; Evangelos Charalambakis; António Dias Da Silva; Davide Di Laurea; Maarten Dossche; Dimitris Georgarakos; Juha Honkkila; Neale O. Kennedy; Geoff Kenny; Aleksandra Kolndrekaj; Justus Meyer; et al. (European Central Bank (ECB), 2021)
The Consumer Expectations Survey (CES) is an important new tool for analysing euro area household economic behaviour and expectations. This new survey covers a range of important topical areas including consumption and income, inflation and gross domestic product (GDP) growth, the labour market, housing market activity and house prices, and consumer finance and credit access. The CES, which was launched as a pilot in January 2020, is a mixed frequency modular survey, which is conducted online. The survey structure and centralised data collection ensures the collection of harmonised quantitative and qualitative euro area information in a timely manner that facilitates direct cross-country comparisons. During the pilot phase, it was conducted for the six largest euro area countries and contained 10,000 individual respondents. In the context of the coronavirus (COVID-19) pandemic, the CES has been used to gather useful information on the impact of the crisis on the household sector and the effectiveness of policy measures to mitigate the effects of the pandemic. The CES also collects information on the public's overall trust in the ECB, their knowledge about its objectives and the channels through which they learn about its monetary policy and other central bank-related topics. This paper describes the key features of this new ECB survey - including its statistical properties - and offers a first evaluation of the results from the pilot phase. It also identifies a number of areas where the survey can be usefully developed further. Overall, the experience with the CES has been very positive, and the pilot survey is considered to have achieved its main objectives.
Keywords: C42; D12; D14; E21; E24; E31; 330; household surveys; expectations; consumer behaviour; micro data set; euro area